In situ structures of the Legionella Dot/Icm T4SS identify the DotA–IcmX complex as the gatekeeper for effector translocation - Jian Yue; Samira Heydari; Donghyun Park; David Chetrit; Shoichi Tachiyama; Wangbiao Guo; Jack M. Botting; Shenping Wu; Craig R. Roy; Jun Liu (Proceedings of the National Academy of Sciences, 2025)
The Dot/Icm machine of Legionella pneumophila is among the most versatile type IV secretion systems (T4SSs), capable of translocating more than 330 distinct effector proteins across the bacterial envelope into host cells. Assembly and function of the system require at least 27 Dot and Icm proteins, yet its architecture and activation mechanism remain poorly understood at the molecular level. Here, we deploy in situ single-particle cryoelectron microscopy to determine near-atomic structures of the Dot/Icm machine and its intimate association with three distinct outer membrane porins in intact bacteria. Notably, two essential yet enigmatic components, DotA and IcmX, form a pentameric protochannel in an inactive state at the central axis of the Dot/Icm machine. Upon Dot/Icm activation with host lysate, this protochannel undergoes extensive rearrangements to generate an extended transenvelope conduit, as visualized by cryoelectron tomography (cryo-ET) and subtomogram averaging. Furthermore, a combination of cryo-ET and cryo-FIB milling of macrophages infected with L. pneumophila reveals tethering of the Dot/Icm machine to the host membrane, suggesting direct translocation of effector proteins from the bacterial cytoplasm into the host. Together, our studies identify the DotA–IcmX complex as a gatekeeper for effector translocation and provide a molecular framework for understanding the assembly and activation of the elaborate Dot/Icm T4SS.